Immunosuppressants in Liver Transplant Recipients With Coronavirus Disease 2019: Capability or Catastrophe?—A Systematic Review and Meta-Analysis - Yadav, Dipesh Kumar; Adhikari, Vishnu Prasad; Ling, Qi; Liang, Tingbo (Frontiers in Medicine, 2021)
Background: The probable impact of the maintenance immunosuppressant (IS) in the liver transplant (LT) recipients with COVID-19 remains unexplored. Our specific aim was to approximate the prognosis of the LT recipients with COVID-19 on the standard maintenance IS. Method: We searched separate databases for the qualified studies in between December 2019 to 25th June 2021. Ultimately, a meta-analysis was carried out using a fixed-effect or random-effect model based on the heterogeneity. Results: With a total of eight studies and 509 LT recipients with COVID-19, the pooled rates of severity and mortality for all the combined IS therapy were 22.4% and 19.5%, respectively. Our study sufficiently showed the IS therapy in the LT recipients with COVID-19 was significantly associated with the non-severe COVID-19 (OR: 11.49 95% CI 4.17-31.65; p< 0.001) and survival of the patients (OR 17.64 95% CI 12.85-24.22; p< 0.001). Moreover, mTORi typically had the lowest rate of severity and mortality compared to the other IS like, CNIs, steroids and antimetabolites, i.e. severity (13.5% vs 21.1%, 24.7% and 26.3%) and mortality (8.3% vs 15%, 17.2% and 12.1%), respectively. Contrary to the general opinions, our meta-analysis showed the comorbidities like, diabetes, hypertension, cardiopulmonary disorders, CKD, age> 60, duration of the LT to the diagnosis of COVID-19, primary disease for the LT, and obesity were not significantly associated with the severity and mortality in the LT recipients with COVID-19 under IS therapy. However, our pooled analysis found the LT recipients with COVID-19 and without comorbidities have a less severe disease and low mortality rate compared to that of the LT recipients with COVID-19 and with comorbidities. Conclusions: In conclusion, LT recipients with COVID‐19 undergoing IS therapies are not significantly associated with the severity and mortality. Therefore, taking the risk of organ rejection into the key consideration, a complete withdrawal of the IS may not be wise. However, MMF might be discontinued or replaced from an IS regimen with the CNIs or mTOR inhibitors based IS therapy in some selected LT recipients with COVID-19, depending upon the severity of the disease.